Dust exposure and respiratory health outcomes in underground miners: Systematic review and meta-analysis - Enoch Nii-Okai; Bright Peter Saah; Elijah Kordieh Mensah; Gopal Fosu Oppong Wiafe (Asian Journal of Toxicology, Environmental, and Occupational Health, 2026)
Background: Underground mining exposes workers to respirable dust, a known cause of various respiratory diseases such as chronic obstructive pulmonary disease (COPD) and pneumoconiosis. Despite extensive research, significant gaps remain in understanding the global impact of dust exposure on miners' health. Method: This systematic review and meta-analysis aimed to assess the impact of dust exposure on respiratory health outcomes among underground miners, focusing on original research articles involving underground miners published between 2000 and 2025. Fifteen studies were included, evaluating outcomes such as lung function decline (FEV₁, FVC), COPD, and pneumoconiosis. Finding: The analysis revealed significant reductions in lung function (FEV₁) linked to dust exposure, with a pooled mean difference of -7.33 (95% CI: -9.93 to -4.72). However, the effect on FVC was minimal. Limitations in study design, including heterogeneous exposure measures and confounding factors, may influence the results. Concusion: Our results underscore the urgent need for enhanced dust control measures, better health surveillance, and stricter regulatory standards to protect miners’ respiratory health. Policymakers and mining companies should prioritize these measures to mitigate the significant health risks posed by dust exposure. Future research should explore the combined effects of dust and other occupational hazards and the long-term effectiveness of mitigation strategies. Novelty/Originality of this article: This study provides an updated meta-analysis encompassing research through 2025, offering a contemporary global perspective on dust-induced lung decline.